The mechanisms of neuropathic pain: an overview for psychiatrists - Pridmore, Saxby A.; Pasha, Iqbal; Kahn, Umeed (University of Goettingen, 2002)
To present an overview of the mechanisms of neuropathic pain. Method: An extensive review of the scientific literature. Results: Neuroplastic changes are described under the headings of: ectopic discharge, sensitizationof sensory terminals, cross-excitation, neurotransmitter change, coupling between the sympathetic and sensory nervous systems, spinal cord reorganization, spinal cord increased excitability, spinal cord decreased inhibition,supraspinal influences. Conclusions: These mechanisms increase our understanding of the patient with neuropathic pain and open the door for therapeutic advances in this field. They also extend our understanding of the nature of the nervous system more generally, and may provide pathophysiologic models of psychiatric disorders